Met-enkephalin modulates the stress responses of plasma concentrations of corticosterone, delta opioid receptor binding, pro-enkephalin expression, and processing in chickens - Pierzchała-Koziec, Krystyna; Scanes, Colin G.; Jaszcza, Klaudia (Frontiers in Physiology, 2026)
IntroductionMet-enkephalin is a neuropeptide whose release into the circulation is enhanced by stress. There have been no studies on the effects of peripherally administered Met-enkephalin in chickens.MethodsThe effects of peripheral administration of Met-enkephalin on the stress response in chickens were investigated measuring plasma concentrations of corticosterone and Met-enkephalin, together with expression of pro-enkephalin (PENK) and delta-opioid binding in the hypothalamus, anterior pituitary and adrenal glands.ResultsAdministration of Met-enkephalin was followed by decreases in the basal and stressed plasma concentrations of the principal glucocorticoid, corticosterone, in chickens. In addition, the increase in plasma concentrations of corticosterone evoked by restraint stress was markedly decreased when the birds were treated with Met-enkephalin. Administration of Met-enkephalin was followed by decreases in PENK expression; hypothalamic, anterior pituitary, and adrenal delta-opioid binding; and plasma concentrations of total Met-enkephalin (peptides containing Met-enkephalin motifs). There were negative relationships between plasma concentrations of corticosterone and Met-enkephalin and between those of native Met-enkephalin and total Met-enkephalin.DiscussionThe ability of Met-enkephalin to attenuate the stress response of corticosterone, and probably other glucocorticoids, is novel and opens up several new lines of inquiry, including its site of action and its source.